PRIVATE INTERNATIONAL LAW / CONFLICT OF LAWS AND DIAMOND TRADE - Fikile Portia Ndlovu (Obiter, 2021)
Any researcher of South African diamond laws would find it inevitable that such research discusses the relationship between international diamond transactions and conflict of laws. This is particularly evident in cases where legal disputes have arisen pertaining to such transactions. This article will make reference to the terms “private international law” and “conflict of laws” interchangeably, although “conflict of laws” will be preferred for reasons of taste rather than logic. The aim of this paper is to illustrate the concept of conflict of laws in general and how it significantly impacts the manner in which courts will ultimately decide on the law to be applied in a matter possibly involving inter alia international diamond transactions. This demonstrates the consistent relevance of conflict of laws particularly in light of the global economy. The correct identification and understanding of conflict of laws’ principles can be stretched to accommodate all other areas of international trade. However, for the purposes of understanding how diamond trade is impacted by conflict of laws in South Africa, this paper will be limited to the legal context of diamond-relevant trade and the latest guidelines provided by our courts in relation to the choice of law in matters where conflict of laws has arisen.